Occupational Safety and Health Hazards Associated with Informal Sector Enterprises at Magaba, Mbare, Harare Zimbabwe - Mandevere, B; Jerie, S (2022)
Occupational safety and health issues are a critical aspect of the developmental agenda in Zimbabwe. This study investigates the hazards associated with the informal sector activities at Magaba in Mbare high density suburb of Harare. To achieve this, interviews and observations were employed in data gathering together with secondary data. The study was conducted at Magaba, situated in Mbare, the oldest high-density suburb in Harare the capital city of Zimbabwe. Findings revealed that the hazards included fires, gas explosions, cuts, violence, noise, falling among others. In order to ameliorate the safety and health risks there is need for the informal enterprise operators to be capacitated and educated on occupational hazards. The responsible authorities need to regard the informal sector enterprises in the same manner as the formal sector by ensuring proper coming up and enforcing of safety legislation.